Antimicrobial Activity of Azithromycin versus Ciprofloxacin in the Treatment of Uncomplicated Enteric Fever in Children and Adolescents: Preclinical Trial: Antimicrobial Activity of Azithromycin Versus Ciprofloxacin for Uncomplicated Enteric Fever - Irfan, Zona; Bijarani, Ali Nawaz; Pervaiz, Yousra Muhammad; Perveen, Fauzia; Shaikh, Shahid Pervez; Arif, Humaira (Pakistan Journal of Health Sciences, 2024)
Typhoid fever, or enteric fever, is an infectious disorder particularly prevalent in Pakistan. Salmonella Typhi is the common and occasionally fatal cause of enteric fever. Objective: To compare the antimicrobial activity of Azithromycin versus Ciprofloxacin in the treatment of uncomplicated enteric fever in children. Methods: This was a comparative cross-sectional study conducted at the Department of Microbiology at Ziauddin University Hospital, Karachi. It lasted six months, from 3 January 2020 to 2 July 2020. There were 152 blood samples in all. According to Clinical and Laboratory Standards Institute guidelines, the antibiotic susceptibility of the isolates was assessed using the Modified Kirby Bauer disc diffusion method on Muller-Hinton agar. Results: When treating typhoid fever in children with simple enteric fever, the susceptibility pattern of Salmonella Typhi revealed that azithromycin was more efficient than ciprofloxacin in preventing the growth of Salmonella Typhi across all samples. Ciprofloxacin showed resistant bacteria. Conclusion: Azithromycin seems to be more clinically effective than ciprofloxacin in treating children’s simple enteric fever when treating typhoid fever.